Case report: Cochlear implantation for deafness caused by endolymphatic sac tumors in patients with von Hippel–Lindau syndrome - Rosiak, Oskar; Pietrzak, Nikodem; Jankowska, Katarzyna; Kucharski, Andrzej; Konopka, Wiesław; Szymański, Marcin (Frontiers in Oncology, 2024)
IntroductionEndolymphatic sac tumors (ELSTs) are rare neuroectodermal neoplasms that originate in the endolymphatic sac and duct. They exhibit no specific age or gender predilection, although they are more prevalent in patients with von Hippel–Lindau syndrome.Material and methodsThe manuscript preparation adhered to the CARE guidelines for standardizing clinical cases and the PRISMA guidelines for scientific reviews. Three studies that met the inclusion criteria were selected from an analysis of 15 articles, supplemented by two additional studies identified through citation review.ResultsThe presented case describes a 16-year-old boy diagnosed with unilateral sensorineural hearing loss secondary to bilateral ELST. Surgical excision of the right ear tumor with simultaneous cochlear implantation was performed, followed by left ear surgery. Hearing restoration was achieved in the implanted right ear, with normal hearing in the left ear, and no postoperative vestibular symptoms were observed.ConclusionPrompt surgical intervention remains the cornerstone of ELST treatment. While cochlear implantation is sporadically reported in scientific literature, it offers a potential option for hearing improvement in patients suffering from deafness caused by the disease.